'Art is not just about entertainment': the social activism and cultural production of Chicago's Inner-City Muslim Action Network (IMAN). Issue 4 (2nd October 2017) - Ali, Muna
Abstract: As cities compete for a 'global city' designation to attract capital, urban policy discourses emphasise fostering 'creative industries' and attracting a 'creative class'. In these discourses, glaring inequalities are often overlooked and religious actors and marginalized communities as creative agents addressing urban problems are conspicuously absent. Exploring IMAN's work, this paper illustrates that the 'global city' presents a strategic space where disempowered actors amplify their impact. In post-9/11 America, Muslim Americans seem to be under siege caught as they are between Islamophobes and terrorists, the state security apparatus, and intra-community divisions. This context has also given rise to creative interventions by Muslim Americans inspired by piety, assertive identities and a passion for social justice. IMAN's faith-based mission envisions transformative changes in Chicago's South side. In its 'Takin' it to the Streets' biennial art and social justice 'urban international' festival and its monthly Community Café, art becomes a creative endeavour and a vehicle for 'powerfully, radically re-imagining the world'. The re-imagining begins with transforming Marquette Park into a creative space for multicultural celebration. Here, jazz, hip-hop, French and Palestinian B-boys encounter Sufi Pakistani music; poetry and comedy entertain and inspire; and religious and civic leaders mobilise attendees to 'Heal the "Hood"'.